Catheter ablation of ventricular arrhythmia originating from isolated outflow tract diverticulum: Two case reports and literature review. Issue 46 (November 2017) - Zhou, Xinbin; Xu, Haibin; Wang, Zhijun
Abstract: Rationale: Congenital ventricular diverticulum is a rare cardiac malformation with a prevalence of about 0.26% in unselected adult patients during other diagnostic procedures. Ventricular arrhythmia originating from outflow tract diverticulum is even rarer and its etiology, epidemiology and proper treatment still remain controversial. Patient concerns: We present 2 cases of isolated outflow tract diverticulum incidentally revealed by cardiac angiography during catheter ablation for ventricular arrhythmia. The diverticulums in both cases were found to be the origins of the arrhythmia. Diagnoses: The 2 patients were both diagnosed with ventricular arrhythmia originating from the outflow tract diverticulum. Interventions: Catheter ablation was successfully performed for case 1 while a conservative observation strategy was chosen for case 2. Outcomes: Case 1 has been asymptomatic and free of premature ventricular contractions (PVCs) and both patients have no cardiac event during observational follow-up for 12 months. Lessons: For ventricular arrhythmia originating from outflow tract diverticulum, catheter ablation may be beneficial and choosing the mouth of the diverticulum or the outflow sites around as the ablation target may be reasonable. An observational follow-up strategy for the small and asymptomatic diverticulum may also be recommended.